PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PERSERTA DIDIK DI SD QUR’AN CENTRE BATAM - Rita, Rita; Oktavianti, Oktavianti (BENING, 2015)
This  study is based on the probelum, How will Waitrs Quality to the Satisfaction of participants Qur’an Centre Elementary Students in Batam, Purpose of this study was to determine the extent of in fluence of the reliability to the satisfaction of students in elementary Qur’an Centre, to determine the extent of the in fluencere sponsiveness to participantsatis faction students in elementary Qur’an Centre, to determine the extent of the in fluence of participantastis faction guarantee to students in elementary Qur’an Centre, to determine the exent of participantastis faction penaruhys empathy for students in elementary Qur’an Centre, to determine the extent of the effect of evidence physical to the satisfaction of participants in elementary learners Qur,an Centre, and to determine the extent of the in fluence of reliabelty, responsiveness,assurance,empathy,and   physicale evidence toget her to the satisfaction of students in elementary scool participants Qur’an Centre, the method used in this study is aquantitative method to analyze the data required.           Subjec is of this study was 100 students in the elementary Qur’an Centre which consists of students of class I,II and III  the data that 1 useprimary data, question in resandsecondary data, the data is collectedirectly from adminitrasion. Based on the analysis of the results obtained there is a positive and significant effect of the variable reliability of the satiftion variable, there is positive and significan variable responivenss to satisfaction, there is a positive and significan timpacton satisfaction guarantee variable, there are significan positive and significan tphyicale vidence of the satisfaction variable, and there is  positive and  significan timpacttoge the rofall independent variable (reliability, responsiveness ,assurance, empathy and tangilbele) on the dependent variable (satisfaction).